MENAKAR RUU KKG DARI PERSPEKTIF KAJIAN HUKUM ISLAM - Najib, Agus Moh. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
The Draft Law on Gender Equality is an early draft at the socialization stage, still to receive inputs from the society. However, there have been many negative responses and many Islamic groups reject it wholesale. Their argument interalia, is that the draft law is secular in nature and is thus contradictory to fundamentalist Islamic teachings and law. This article will attempt to discuss and position the draft law within the ambit of Islamic law. The general conclusion is that while most of the ideas contained within the draft law is much in line with the principles of Islamic law, several articles which conflict with Islamic law need to be revised and changed. The shortcomings and errors within the draft law are indeed in need of criticism, but it should not be a reason to reject the entire draft law